Force-mediated kinetics of single P-selectin/ligand complexes observed by atomic force microscopy - Fritz, Jürgen (The National Academy of Sciences, 1998)
Leukocytes roll along the endothelium of postcapillary venules in response to inflammatory signals. Rolling under the hydrodynamic drag forces of blood flow is mediated by the interaction between selectins and their ligands across the leukocyte and endothelial cell surfaces. Here we present force-spectroscopy experiments on single complexes of P-selectin and P-selectin glycoprotein ligand-1 by atomic force microscopy to determine the intrinsic molecular properties of this dynamic adhesion process. By modeling intermolecular and intramolecular forces as well as the adhesion probability in atomic force microscopy experiments we gain information on rupture forces, elasticity, and kinetics of the P-selectin/P-selectin glycoprotein ligand-1 interaction. The complexes are able to withstand forces up to 165 pN and show a chain-like elasticity with a molecular spring constant of 5.3 pN nm(−1) and a persistence length of 0.35 nm. The dissociation constant (off-rate) varies over three orders of magnitude from 0.02 s(−1) under zero force up to 15 s(−1) under external applied forces. Rupture force and lifetime of the complexes are not constant, but directly depend on the applied force per unit time, which is a product of the intrinsic molecular elasticity and the external pulling velocity. The high strength of binding combined with force-dependent rate constants and high molecular elasticity are tailored to support physiological leukocyte rolling.